Experimental results from a stepped frequency GPR - G. M. Signore; M. Sacchettino; R. Persico; G. Galiero; L. Ciofaniello; G. Alberti; S. Vetrella (Annals of Geophysics, 2003)
In the framework of a nationally funded project, a Ground Penetrating Radar (GPR) has been developed by
the Italian Consortium for Research on Advanced Remote Sensing Systems (CO.RI.S.T.A.). The system was
described in a previous paper (Alberti et al., 2002). As new aspects, the system is a stepped frequency GPR that
can work both in gated and ungated mode, and the antennas can be moved automatically in a controlled fashion.
As aspects of geophysical interest, the system is exploitable in situations wherein a high resolution and a shallow
penetration in the soil (a few meters) are required. Possibly, this is an example of probing a landscape. This paper
completes the results of Alberti et al. (2002), wherein laboratory tests where described, by providing the main
results obtained during an outdoor experimental campaign, performed fi rst in a controlled site and then in an
archaeological site.